Medicinal Plant-derived Compounds as Potential Phytotherapy for COVID-19 Disease: A Review - M. El-Darier, Salama; Rashed, Suzan A.; Fayez, Ayat; Hassanein, Sarah S.; R. Sharaby, Muhammed; Tawfik, Noran M.; Mansour, Heba; Adel, Mohamed (Current Aspects in Pharmaceutical Research and Development Vol. 7, 2022)
Currently, the human being faces a contagious virus called SARS-CoV-2 with a high transmission ability, infection, and a relatively high mortality rate, especially for the elderly. General symptoms of the disease involve fever, sore throat, pneumonia, cough, headache, diarrhea, muscle pain, shortness of breath, renal failure, and even death. All research interest is directed to finding a drug or vaccine to save millions of people’s lives; some have succeeded and applied now in some countries. Medicinal plants represent a green treasure that renders plentiful primary and secondary metabolites characterized by potent biological activities. Interestingly, the secondary metabolites, alkaloids, flavonoids, tannins, and terpenoids, own a broad antiviral history. The plant antiviral capabilities may be due to inhibition of viral attachment to/penetration of the host cell; inhibition of the virus replication; suppressing RNA replication; down regulation of viral proteins translation; interfering with virus non-structural/structural protein; down regulation of virus-induced pro-inflammatory/inflammatory signaling pathways in the host cell, and antioxidant activity thus abating the virus-induced oxidative stress effect. Presently, as we are trapped with a surly virus, there are attempts to exploit the power of nature. Therefore, the main objective of this review is to refer to some medicinal plants or their derivatives that limit the virus’s virulence or alleviate the symptoms associated with this virus.